2015
DOI: 10.1371/journal.pone.0139585
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Reconstruction of Paternity in European Lobsters (Homarus gammarus)

Abstract: Decapod crustaceans exhibit considerable variation in fertilisation strategies, ranging from pervasive single paternity to the near-ubiquitous presence of multiple paternity, and such knowledge of mating systems and behaviour are required for the informed management of commercially-exploited marine fisheries. We used genetic markers to assess the paternity of individual broods in the European lobster, Homarus gammarus, a species for which paternity structure is unknown. Using 13 multiplexed microsatellite loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 61 publications
0
14
1
Order By: Relevance
“…Protocols for DNA extraction, primer synthesis, multiplexed PCR amplification of loci, fragment analysis and allele sizing followed those outlined in Ellis et al (2015c). Individuals were each screened at 15 microsatellites -12 from André & Knutsen (2010) …”
Section: Sample Collection and Microsatellite Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Protocols for DNA extraction, primer synthesis, multiplexed PCR amplification of loci, fragment analysis and allele sizing followed those outlined in Ellis et al (2015c). Individuals were each screened at 15 microsatellites -12 from André & Knutsen (2010) …”
Section: Sample Collection and Microsatellite Genotypingmentioning
confidence: 99%
“…The locus HGA8 was found to be significantly deficient in heterozygotes, both globally (p < 0.001) and within the majority of geographic samples. This was the result of the failure of one or more alleles to amplify; null alleles at HGA8 were estimated to have a global frequency of 0.08, a maximum frequency of 0.2 among geographic samples, and were confirmed via a separate parentage analysis (Ellis et al 2015c). As a result, data for this locus were removed from the dataset ahead of analysis.…”
Section: Loci Screening and Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Parentage studies have revealed that polyandry is widespread in decapods and that there is substantial variation in the extent of multiple paternity within and among species, ranging from zero in the European lobster, Homarus gammarus (Ellis et al, 2015) to 100% in the squat lobster, Munida sarsi (Bailie, Hynes, & Prodohl, 2011). For the most part, however, parentage studies on decapods have been conducted on crabs (Baggio et al, 2011;Jensen & Bentzen, 2012;Jossart et al, 2014;Koga, Henmi, & Murai, 1993;McKeown & Shaw, 2008;Pardo, Riveros, Fuentes, Rojas-Hernandez, & Veliz, 2016;Reaney, Maurer, Backwell, & Linde, 2012;Sainte-Marie, Gosselin, Sevigny, & Urbani, 2008).…”
mentioning
confidence: 99%
“…By comparison, we know little about the mating system of lobsters (Ellis et al, 2015;Gosselin et al, 2005;Melville-Smith, de Lestang, Beale, Groth, & Thompson, 2009;Streiff, Mira, Castro, & Cancela, 2004), especially regarding female mating strategies and the prevalence of polyandry and multiple paternity in natural populations.…”
mentioning
confidence: 99%